Creativity in Dissent: From the politics of pedagogy to the art of pedagogy - Soon, Simon (Center for Southeast Asian Studies, Kyoto University, 2018)
This essay examines the historical conditions of the politics of pedagogy that have shaped the history of postcolonial higher education and attempts at producing coun-termovements to its subsequent institutionalization. I consider this in relation to pedagogical practices that reference creative forms in avant-garde art and theater. A genealogy of rethinking education through creative means can be traced back to the establishment of Nanyang University and the teaching of contemporary Asian literature by Han Suyin, with later artists such as Wong Hoy Cheong engaging with Paulo Freire’s ideas on learning in Wong’s course on Third World aesthetics, Universiti Bangsar Utama’s reimagination of the role that education could play in Kuala Lumpur during the 1998 Reformasi, and most recently Buku Jalan’s decenter-ing of education. Finally, I consider the pedagogical stakes at hand by exploring the life story of a bookseller in Kelantan and his embodiment of a local cosmopolitanism.